PERILAKU SEKSUAL REMAJA DITINJAU DARI FREKUENSI DALAM MENGAKSES KONTEN PORNOGRAFI - Cahyadi, Andi (Widya Warta, 2019)
This study aimed to determine the relationship between the frequency of accessing pornographic content towards adolescents sexual behavior. The subjects of this study were 90 adolescent students who attendedCatholicPharmacy vocational school of Bina Farma Madiun. The measuring instrument used was the scale of frequency in accessing pornographic content and the scale of adolescentssexual behavior. Data analysis method used in this research was regression analysis of SPSS program version 22. Based on the results of calculation analysis obtained there was a correlation coefficient r = 0,042, in which RÂ² = 0,034. This meant that there was a positive relationship between adolescents sexual behavior with frequency in accessing pornographic content, with effective contribution variable of 3.4%.